HUBUNGAN SERTIFIKSI DENGAN PERUBAHAN KINERJA GURU DI SMA NEGERI 2 KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Ekrawati, Ekrawati; Ansofino, Ansofino; Areva, Desi (Pendidikan Ekonomi, 2014)
ABSTRACTÂ This research was conducted at SMAN 2 Koto XI Tarusan where the population is all teachers who are already certified and sampling techniques using total sampling . Data were collected through questionnaires or questionnaire . Data were analyzed with multiple linear regression method .The results showed that : 1 ) there is a significant correlation between the changes in pedagogical teacher performance , meaning that if the pedagogical increased by 1 % then the regression coefficient increased by 0.093 . 2 ) there is a significant relationship between personal competence to changes in teacher performance , meaning when personal competence increases 1 % then the regression coefficient increased by 0.239 . 3 ) there is a significant relationship between social competence to changes in teacher performance , meaning that if the social competence increased by 1 % then the regression coefficient increased by 0.423 . 4 ) there is a significant relationship between the professional competence of the teacher s performance changes , meaning that if the professional competence increased by 1 % then the regression coefficient increased by 0.380 . 5 ) there is a significant relationship between pedagogical simultaneously , personality , social , professional to changes in teacher performance , meaning that if the overall competence increased by 1 % then the regression coefficient increased by 0.837 . This can be proved by the results of research that states that the calculated F value ( 34.772 ) > Ftable ( 2.947 ) and significant ( 0.000 ) < Alpha ( 0.05 ) means it can be concluded that there is a significant relationship between pedagogic competence , personality , social and professional performance simultaneously with changes in teacher certification in SMA N 2 Koto XI Tarusan South Coastal District in the amount of 83.7 % while the remaining 16.3 % .Â